Sharing for Sheep - Davidson, Zanna; Friend, Alison; Blore, Tabitha; Sims, Lesley (London : Usborne Publishing Ltd., 2023)
"A hilarious, rhyming adventure about sharing. A bright, engaging story to encourage sharing. Did you know when you're not looking, sheep are knitting lots of things... from toys to scarves to mittens, to hats and woolly wings! But then, disaster strikes, when two competitive sheep discover they are knitting from the SAME ball of wool. Sharing just might be the only way to save the day"--Publisher's description
Keywords: Children's stories -- Pictorial works; Sheep -- Juvenile fiction; Sharing -- Juvenile fiction; Knitting -- Juvenile fiction; Picture books